Antibacterial water permeable brick and preparation method thereof
By using antibacterial and anti-moss-resistant materials such as flash furnace water-quenched copper slag, nano-titanium dioxide, and nano-zinc oxide in permeable bricks, the growth of microorganisms is inhibited through the release of copper ions and photocatalysis, thus solving the problem of moss growth on the surface of permeable bricks and improving permeability and structural stability.
Patent Information
- Application Number
- CN202511217056.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-28
- Publication Date
- 2025-11-28
AI Technical Summary
Existing permeable bricks are prone to the growth of moss and algae on their surface, leading to safety hazards and reduced permeability. Furthermore, microbial metabolic products affect structural stability.
Antibacterial and anti-moss materials are used, including flash furnace water-quenched copper slag, nano titanium dioxide and nano zinc oxide. The release of copper ions and photocatalysis inhibit the growth of microorganisms, keeping the brick clean and permeable.
It effectively prevents moss growth, reduces the risk of slipping, improves the service life and permeability of permeable bricks, and ensures the stability of the paving structure.
Abstract
Description
Technical Field
[0001] This invention relates to the field of permeable brick technology, specifically to an antibacterial permeable brick and its preparation method. Background Technology
[0002] Permeable bricks allow rainwater to quickly flow into the ground, effectively replenishing groundwater, alleviating urban flooding and the "heat island effect," and promoting water circulation. However, due to their internal structure containing numerous interconnected pores, their surfaces are usually not perfectly smooth (to increase friction and facilitate permeability). This rough surface and crevices easily trap and accumulate airborne moss spores, algal cells, tiny organic particles, dust, leaf debris, animal excrement, and oil spills from vehicles. During rainfall or watering, they rapidly absorb water and can store it for extended periods inside the brick and in the underlying bedding layer. Even after the weather clears, the moisture inside the brick slowly evaporates to the surface (capillary action), causing the brick surface and its crevices to remain damp for a long time. These deposits are decomposed by rainwater infiltration or microbial action, gradually forming a "micro-soil layer" rich in nutrients such as nitrogen, phosphorus, and potassium on the brick surface or near the pores. The persistent environment causes permeable bricks to grow large amounts of moss, lichen, and algae (commonly known as "green moss"), affecting their aesthetics. Areas with moss, lichen, and algae become extremely slippery after rain, posing a serious safety hazard. This is especially true in areas requiring slip resistance, such as ramps, steps, and sidewalks, where moss growth significantly increases the risk of pedestrians slipping. Furthermore, the metabolic activity of moss and algae can further corrode the brick surface, reducing the lifespan and permeability of the permeable bricks, thus affecting their drainage performance. In long-term humid environments, the brick structure may also deteriorate due to the accumulation of microbial metabolic products, thereby affecting the overall stability of the paving structure. Therefore, to avoid the shortcomings of existing technologies, it is necessary to improve them. Summary of the Invention
[0003] The purpose of this invention is to overcome the shortcomings and deficiencies of the prior art and to provide an antibacterial permeable brick and its preparation method.
[0004] This invention is achieved through the following technical solution: An antibacterial permeable brick is prepared from the following raw materials, which include coarse aggregate, fine aggregate, antibacterial and anti-moss material, cementing material and additives. The antibacterial and anti-moss material includes flash furnace water-quenched copper slag, nano titanium dioxide and nano zinc oxide.
[0005] Furthermore, the coarse aggregate accounts for 60% to 80% of the raw materials by mass percentage, the fine aggregate accounts for 20% to 40% of the raw materials by mass percentage, the coarse aggregate has a mesh size of 5 to 20 mesh, and the fine aggregate has a mesh size of 20 to 120 mesh.
[0006] Furthermore, the coarse aggregate includes solid waste ceramic bricks or recycled stone, and the fine aggregate includes solid waste ceramic bricks or recycled stone.
[0007] Furthermore, the flash furnace water-quenched copper slag accounts for 15% to 25% of the raw materials by mass percentage.
[0008] Furthermore, the cementing material includes silicate cement, silica fume, and fly ash.
[0009] Furthermore, the silicate cement accounts for 12% to 25% of the raw materials by mass percentage.
[0010] Furthermore, the admixture materials include high-efficiency water-reducing agents, redispersible latex powder, retarder, and expansion agent.
[0011] A method for preparing an antibacterial permeable brick includes the following steps: Step 1: Crush and screen the coarse aggregate into two mesh sizes: 5-10 mesh and 10-20 mesh. Crush and screen the fine aggregate into three mesh sizes: 20-40 mesh, 40-70 mesh, and 70-120 mesh. Step 2: Weigh coarse aggregates and fine aggregates of different mesh sizes and flash furnace water-quenched copper slag in proportion and feed them into the mixer; Step 3: After adding water and high-efficiency water-reducing agent and stirring, add silicate cement, silica fume, fly ash, nano titanium dioxide, nano zinc oxide, redispersible latex powder, retarder, and expansion agent and stir thoroughly until uniform. Step 4: Feed the well-stirred mixture into the permeable brick forming machine for molding; Step 5: After molding, the product is sent to the curing room for several hours of curing, then sorted and packaged, and naturally cured for several days to obtain the finished product.
[0012] Furthermore, in step two, the stirring time is 1 to 3 minutes, and in step three, the stirring time of water and high-efficiency water-reducing agent is 2 to 4 minutes.
[0013] Furthermore, in step five, the curing time in the curing room is 18 to 33 hours, and the natural curing time is 20 to 36 days.
[0014] Compared to existing technologies, this invention utilizes raw materials including antibacterial and anti-moss materials. These materials comprise flash furnace water-quenched copper slag, nano-titanium dioxide, and nano-zinc oxide. The flash furnace water-quenched copper slag releases copper ions that provide long-lasting bactericidal and antibacterial effects, preventing the growth of microorganisms and moss. Nano-titanium dioxide has antibacterial properties; under light, it can destroy bacterial cell membranes and coagulate viral proteins, thereby inhibiting viral activity and killing microorganisms. This prevents the accumulation of microbial metabolites, which could lead to deterioration and affect the overall stability of the paving structure. Due to the photocatalytic activity of nano-titanium dioxide, it can decompose organic and inorganic matter on the surface, keeping the permeable brick surface clean and smooth, and preventing moss growth. Nano-zinc oxide also possesses good antibacterial properties. Yes, nano zinc oxide has a strong adsorption capacity, which can adsorb harmful substances from bacteria and render them inactive, thereby achieving sterilization. It also has a strong destructive effect on moss spores. Nano zinc oxide has good photocatalytic properties. When exposed to external light, it can produce an active substance with electrons and holes. This active substance can react with the cell wall or membrane of bacteria, leading to their destruction and death. The photocatalytic effect of nano zinc oxide can also decompose pollutants, which is beneficial for protecting permeable bricks, keeping the surface of permeable bricks clean and smooth, effectively preventing the growth of moss, reducing the risk of pedestrians slipping, preventing the metabolic activity of moss from corroding the brick surface, improving the service life and permeability of permeable bricks, improving their drainage effect, and ensuring the stability of the overall paving structure. Detailed Implementation
[0015] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0016] An antibacterial permeable brick is prepared from the following raw materials, including coarse aggregate, fine aggregate, antibacterial and anti-moss materials, cementing materials and additives. The antibacterial and anti-moss materials include flash furnace water-quenched copper slag, nano titanium dioxide and nano zinc oxide.
[0017] Coarse aggregate accounts for 60% to 80% of the raw materials by mass percentage, while fine aggregate accounts for 20% to 40% by mass percentage. The mesh size of coarse aggregate is 5 to 20 mesh, and the mesh size of fine aggregate is 20 to 120 mesh. Different mesh sizes of coarse and fine aggregate can improve the quality stability and permeability of permeable bricks.
[0018] Coarse aggregates include solid waste ceramic bricks or recycled stone, while fine aggregates also include solid waste ceramic bricks or recycled stone. The materials are low-cost and produce a stable structure after molding.
[0019] Flash furnace water-quenched copper slag accounts for 15% to 25% of the raw materials by weight. It can effectively loosen the internal structure of permeable bricks, which is conducive to the drainage and evaporation of water and avoids the growth of microorganisms and moss.
[0020] Cementing materials include silicate cement, silica fume, and fly ash, which facilitate the bonding of permeable brick materials and improve structural stability.
[0021] Silicate cement accounts for 12% to 25% of the raw materials by weight, which makes the permeable brick material easy to bond and improves the structural stability.
[0022] The admixtures include high-efficiency water-reducing agents, redispersible latex powder, retarders, and expansion agents, which can effectively improve the performance of permeable bricks.
[0023] A method for preparing an antibacterial permeable brick includes the following steps: Step 1: Crush and screen the coarse aggregate into two mesh sizes: 5-10 mesh and 10-20 mesh. Crush and screen the fine aggregate into three mesh sizes: 20-40 mesh, 40-70 mesh, and 70-120 mesh. Step 2: Weigh coarse aggregates and fine aggregates of different mesh sizes and flash furnace water-quenched copper slag in proportion and feed them into the mixer; Step 3: After adding water and high-efficiency water-reducing agent and stirring, add silicate cement, silica fume, fly ash, nano titanium dioxide, nano zinc oxide, redispersible latex powder, retarder, and expansion agent and stir thoroughly until uniform. Step 4: Feed the well-stirred mixture into the permeable brick forming machine for molding; Step 5: After molding, the product is sent to the curing room for several hours of curing, then sorted and packaged, and naturally cured for several days to obtain the finished product.
[0024] In step two, the stirring time is 1 to 3 minutes. In step three, the stirring time of water and high-efficiency water-reducing agent is 2 to 4 minutes. The coarse aggregate, fine aggregate and flash furnace water-quenched copper slag are fully and evenly mixed. The high-efficiency water-reducing agent has strong dispersibility of material particles, high water reduction rate and good early strength enhancement effect.
[0025] In step five, the curing time in the curing room is 18 to 33 hours, and the natural curing time is 20 to 36 days, gradually forming a permeable brick with a stable structure.
[0026] Compared to existing technologies, this invention utilizes raw materials including antibacterial and anti-moss materials. These materials comprise flash furnace water-quenched copper slag, nano-titanium dioxide, and nano-zinc oxide. The copper ions released from the flash furnace water-quenched copper slag have a long-lasting bactericidal and antibacterial effect, preventing the growth of microorganisms and moss. Nano-titanium dioxide has antibacterial properties; under light, it can destroy bacterial cell membranes and coagulate viral proteins, thereby inhibiting viral activity and killing microorganisms. This prevents the accumulation of microbial metabolites, which could lead to deterioration and affect the stability of the overall paving structure. Due to the photocatalytic activity of nano-titanium dioxide, it can decompose organic and inorganic matter on the surface, keeping the permeable brick surface clean and smooth, and preventing moss growth. Nano-zinc oxide also has good antibacterial properties. Nano zinc oxide has a strong adsorption capacity, which can adsorb harmful substances from bacteria and render them inactive, thereby achieving sterilization. It also has a strong destructive effect on moss spores. Nano zinc oxide has good photocatalytic properties. When exposed to external light, it can produce an active substance with electrons and holes. This active substance can react with the cell wall or membrane of bacteria, leading to their destruction and death. The photocatalytic effect of nano zinc oxide can also decompose pollutants, which is beneficial to protecting permeable bricks, keeping the surface of permeable bricks clean and smooth, effectively preventing the growth of moss, reducing the risk of pedestrians slipping, preventing the metabolic activity of moss from corroding the brick surface, improving the service life and permeability of permeable bricks, improving their drainage effect, and ensuring the stability of the overall paving structure.
[0027] Detailed introduction to the antibacterial properties of nano zinc oxide (ZnO) (antibacterial mechanism: triple synergistic effect): 1. Zinc ion dissolution (chemical reaction): When nano-ZnO comes into contact with water or bacteria, it slowly releases Zn²⁺ ions. After penetrating the cell membrane, these ions bind to bacterial proteases (such as enzymes containing -SH groups), inactivating them and blocking ATPase activity; they also disrupt the electron transport chain, interfering with energy metabolism. Features: Zn²⁺ can be reused after sterilization, providing long-lasting antibacterial effects.
[0028] 2. Reactive oxygen species (ROS) oxidation (photocatalysis): Under ultraviolet or visible light excitation (especially wavelength <400nm): electron-hole pairs (e⁻ / h⁺) migrate to the surface and react with H₂O / O₂ to generate strong oxidizing ROS such as ·OH, H₂O₂, and O₂⁻. ROS attack cell membrane lipids, proteins, and DNA, leading to intracellular leakage and DNA breakage. Note: Rare earth doping (such as Ce³⁺ / Nd³⁺) can extend the photoresponse to the visible light region (520nm), improving efficiency in low-light environments.
[0029] 3. Physical damage (mechanical action): Positively charged nanoparticles (surface potential +24mV) electrostatically attract negatively charged bacterial membranes (such as E. coli), directly piercing the cell wall; the nanoscale rough surface exacerbates mechanical damage, leading to leakage of contents.
[0030] Detailed introduction to the antibacterial mechanism of nano-titanium dioxide (TiO2) (antibacterial mechanism: photocatalytic generation of reactive oxygen species (ROS)): When nano-titanium dioxide (TiO2) is exposed to light (especially ultraviolet light), its valence band electrons transition to the conduction band, forming electron-hole pairs. These charge carriers react with adsorbed water or oxygen on the surface to generate highly oxidizing reactive oxygen species. Hydroxyl radicals (·OH): attack unsaturated bonds in bacterial cell membranes and disrupt lipid structures.
[0031] Superoxide anion (O2⁻·): Oxidizes proteins and enzymes in bacteria, interfering with metabolic functions.
[0032] Hydrogen peroxide (H2O2): penetrates the cell wall, causing leakage of intracellular substances.
[0033] This process requires no chemical additives and completely decomposes bacteria through physical oxidation, thus avoiding the development of drug resistance.
[0034] Sources and characteristics of flash furnace water-quenched copper slag 1. Formation process: During the smelting of copper concentrate in a flash furnace, the molten slag produced is rapidly cooled by water to form granular solids (water-quenched slag). Its main components are fir olivine (2FeO·SiO2), magnetite (Fe3O4), and glassy silicates, while small amounts of copper (usually containing >0.5%) and other metallic elements (such as zinc, nickel, etc.) remain.
[0035] Physical structure: The water quenching process causes the copper slag to form an amorphous or microcrystalline glassy structure with a large specific surface area and high surface activity, which is conducive to the dissolution of copper ions.
[0036] 2. Antibacterial mechanism of copper Ion release and oxidative damage: Trace amounts of copper in copper slag are slowly released in ionic form (Cu⁺ / Cu²⁺). After penetrating the bacterial cell membrane, copper ions bind to intracellular enzymes, inactivating them, and catalyze the production of reactive oxygen species (ROS), which damage DNA / RNA structures, leading to bacterial death.
[0037] Contact killing effect: When copper slag particles come into direct contact with microorganisms, the cell membrane integrity is disrupted through electrostatic interaction. Experiments show that copper-containing materials can achieve a kill rate of over 99% against common pathogens such as Escherichia coli and Staphylococcus aureus.
[0038] 3. Antibacterial potential of water-quenched copper slag Long-lasting effect and stability: Copper in copper slag exists in the form of sulfides (such as Cu2S) or oxides, and can continuously release low concentrations of copper ions in humid environments, providing a long-lasting antibacterial effect. Even if the surface oxidizes and discolors, the antibacterial properties remain stable.
[0039] Synergistic enhancement effect: Trace elements such as zinc and silver in the slag can enhance the antibacterial effect. For example, zinc ions can destroy bacterial biofilms and produce a synergistic antibacterial effect with copper.
[0040] 4. Application Scenarios and Challenges In the building materials sector: Adding copper slag as an aggregate to concrete, tiles, or coatings can give building materials self-cleaning and antibacterial properties, making them suitable for public health facilities such as hospitals and schools.
[0041] Environmental and safety constraints: Excessive leaching of copper ions must be controlled (e.g., through surface coating technology) to avoid toxic risks to aquatic ecosystems. Furthermore, the slag may contain harmful impurities such as lead and arsenic, requiring pretreatment to ensure safety.
[0042] 5. Future Research Directions Material modification: Valuable metals are extracted from copper slag by acid leaching or bioleaching, and copper nanoparticles or copper-based composite materials are synthesized to improve antibacterial efficiency.
[0043] Circular economy integration: Combining the resource utilization of copper slag in building materials, soil improvement and other fields to achieve the dual goals of "value-added solid waste + antibacterial function".
[0044] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. An antibacterial permeable brick, characterized in that: It is prepared from the following raw materials, which include coarse aggregate, fine aggregate, antibacterial and anti-moss material, cementing material and additives. The antibacterial and anti-moss material includes flash furnace water-quenched copper slag, nano titanium dioxide and nano zinc oxide.
2. The antibacterial permeable brick according to claim 1, characterized in that: The coarse aggregate accounts for 60% to 80% of the raw materials by mass percentage, and the fine aggregate accounts for 20% to 40% of the raw materials by mass percentage. The coarse aggregate has a mesh size of 5 to 20 mesh, and the fine aggregate has a mesh size of 20 to 120 mesh.
3. The antibacterial permeable brick according to claim 1, characterized in that: The coarse aggregate includes solid waste ceramic bricks or recycled stone, and the fine aggregate includes solid waste ceramic bricks or recycled stone.
4. The antibacterial permeable brick according to claim 1, characterized in that: The flash furnace water-quenched copper slag accounts for 15% to 25% of the raw materials by mass percentage.
5. The antibacterial permeable brick according to claim 1, characterized in that: The cementing materials include silicate cement, silica fume, and fly ash.
6. The antibacterial permeable brick according to claim 5, characterized in that: The silicate cement accounts for 12% to 25% of the raw materials by mass percentage.
7. The antibacterial permeable brick according to claim 1, characterized in that: The admixture materials include high-efficiency water-reducing agents, redispersible latex powder, retarders, and expansion agents.
8. A method for preparing an antibacterial permeable brick, characterized in that: Includes the following steps: Step 1: Crush and screen the coarse aggregate into two mesh sizes: 5-10 mesh and 10-20 mesh. Crush and screen the fine aggregate into three mesh sizes: 20-40 mesh, 40-70 mesh, and 70-120 mesh. Step 2: Weigh coarse aggregates and fine aggregates of different mesh sizes and flash furnace water-quenched copper slag in proportion and feed them into the mixer; Step 3: After adding water and high-efficiency water-reducing agent and stirring, add silicate cement, silica fume, fly ash, nano titanium dioxide, nano zinc oxide, redispersible latex powder, retarder, and expansion agent and stir thoroughly until uniform. Step 4: Feed the well-stirred mixture into the permeable brick forming machine for molding; Step 5: After molding, the product is sent to the curing room for several hours of curing, then sorted and packaged, and naturally cured for several days to obtain the finished product.
9. The method for preparing antibacterial permeable bricks according to claim 1, characterized in that: In step two, the stirring time is 1 to 3 minutes, and in step three, the stirring time of water and high-efficiency water-reducing agent is 2 to 4 minutes.
10. The method for preparing antibacterial permeable bricks according to claim 1, characterized in that: In step five, the curing time in the curing room is 18 to 33 hours, and the natural curing time is 20 to 36 days.